(untitled) (Research, Society and Development, 2022)
With the development of aesthetic dentistry in search of minimally invasive procedures, the demands for a harmonious rehabilitative treatment have been increasingly detailed in pursuit of success. The aim of this article is to present a current narrative review on the comparison between the longevity of rehabilitative treatment with direct and indirect veneers in anterior teeth. The present study was carried out through a search for scientific articles in the Pubmed database, having as eligibility criteria the clinical assessment of the longevity of direct and indirect veneers in anterior teeth. As exclusion criteria, studies that evaluated restorations in posterior teeth, laboratory studies and literature reviews were excluded. The use of direct and indirect restorations provides a treatment with greater clinical longevity, fracture resistance, color stability, in addition to favoring the aesthetics and biocompatibility of the same. However, direct composite resin veneers showed greater instability in color, however, they presented advantages such as the ease of handling shape and color, allowing a better ease at the time of rehabilitation. Porcelain indirect veneers offer the patient greater strength and greater color stability, in addition to being manufactured extra-orally, it does not interfere with the advantages it offers in the treatment. It is concluded that indirect veneers on anterior teeth showed a relatively longer survival when compared to direct restorations.